Implementation of Management Functions in Economic Recovery in the Tourism Village of Babalan Lor Village - Haikhal, Fikri; Irawan, Soni; Maulana, M. Mirza; Hidayatullah, Ahmad (Munazzama: Journal of Islamic Management and Pilgrimage, 2023)
This article was written to find out about the implementation of the economic recovery management function in the tourist village of Babalan Lor Village, Bojong District. Hence, the information can be deciphered regarding the implementation of economic recovery carried out by the residents of the tourist village in Babalan Lor Village. The problem of this study was how the strategy was applied by the tourism village community in recovering the economy through the management function. The method used in this study was a qualitative approach as the qualitative components include observation, interviews, and literature research. The results of the study showed that the residents of tourist village carry out a management function; they are the principles of planning, organizing, actuating and controlling as a strategy in recovering the economy.